On-farm culture and pathogen identification: risks and benefits. (2nd November 2021) - Manning, Al
Abstract : Selective treatment of clinical mastitis cases based on the results of on-farm culture (OFC) has been suggested by several international experts. It is based on the theory that mastitis cases caused by Gram-negative species has high resolution rates, and those that do not resolve respond poorly to therapy. Several peer-reviewed studies have evaluated the accuracy of different OFC test kits, which are between 60–85% accurate at identifying Gram-positive pathogens. Implementation studies consistently show a reduction in antimicrobial use, although further research across larger populations is needed to assess the impact on mastitis cure. Any OFC protocol should be regularly reviewed with the herd veterinarian. Herds with a high bulk cell count, a high prevalence of Gram-positive pathogens (e.g. Streptococcus uberis ), or with a high prevalence of Klebsiella spp. should carefully consider the impact of deferred or withholding treatment on mastitis cure.